Students' Writing Ability In Descriptive Text At The Tenth Grade Of AL-MUHSININ Islamic Boarding School - M. Hafizul Aldi (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2025)
This study aimed to analyze the writing ability of tenth grade students at Al-Muhsinin Boarding School in composing descriptive texts. The research used a quantitative approach and using research design was descriptive. Collecting data through writing test. The finding showed that most students demonstrate a moderate level of writing proficiency, with strengths in vocabulary usage and sentence structure. However, common difficulties are found in the areas of grammar accuracy, organization of ideas, and use of cohesive devices. The result of the test of student’s writing ability in descriptive text 11 students got good category. The study concluded that while students have a basic understanding of descriptive writing, more focused instructional strategies are needed to enhance their writing quality.